2013
DOI: 10.1002/eji.201242765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of the HIF‐1α isoform I.1 in T cells enhances antibacterial immunity and improves survival in a murine peritonitis model

Abstract: Summary Hypoxia-adenosinergic suppression and re-direction of the immune response has been implicated in the regulation of anti-pathogen and anti-tumor immunity, with Hypoxia-inducible factor 1α (HIF-1α) playing a major role. In this study, we investigated the role of isoform I.1, a quantitatively minor alternative isoform of HIF-1α, in anti-bacterial immunity and sepsis survival. By using the cecal ligation and puncture model of bacterial peritonitis we studied the function of I.1 isoform in T cells using mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…These observations indicated that hypoxia inhibited Th1-type cell activation and were consistent with an earlier report of increased inflammation and autoimmunity in chimeric mice with HIF-1α deletion in cells of the adaptive immune system [52]. Another study highlights the immunosuppressive role of the activation-inducible isoform HIF-1α isoform I.1 in T cells during bacterial sepsis [53]. In addition, recent evidence suggests that hypoxia may differentially regulate the balance of Th17/Treg cells in vivo [54].…”
Section: T Lymphocytessupporting
confidence: 88%
“…These observations indicated that hypoxia inhibited Th1-type cell activation and were consistent with an earlier report of increased inflammation and autoimmunity in chimeric mice with HIF-1α deletion in cells of the adaptive immune system [52]. Another study highlights the immunosuppressive role of the activation-inducible isoform HIF-1α isoform I.1 in T cells during bacterial sepsis [53]. In addition, recent evidence suggests that hypoxia may differentially regulate the balance of Th17/Treg cells in vivo [54].…”
Section: T Lymphocytessupporting
confidence: 88%
“…These included hif1a exon I.1 (albeit weakly expressed, as judged by Nanostring absolute RNA counts (data not shown)), hif2a , vegfa , glut1 , entpd1 (CD39), galectin3 , gelsolin , and tnfrsf9 (CD137). However, hif1a , adora2a (A2AR), and hif1b were not modulated, hif3a was not expressed, while nt5e (CD73) was downregulated (Fig. A).…”
Section: Resultsmentioning
confidence: 97%
“…As IL-17 has been shown to inhibit IFNγ production, it has been proposed that the increase in IFNγ in these mice is due to decreased IL-17 production 55 . Nonetheless, follow-up studies have revealed that deletion of the HIF1α isoform I.1 in T cells enhances immunity in a model of bacterial infection 61 . Therefore, the precise role of HIF1α in T H 1 and T H 2 cell differentiation and function remains to be determined.…”
Section: Metabolic Regulation Of Cd4+ Th Cell Lineagesmentioning
confidence: 99%